(untitled) (Sains Humanika, 2014)
Total quality management (TQM) and knowledge management (KM) assist to grow an organization, but the acquisition of human values which are tacit knowledge by nature for TQM implementation are critical. It is agreeable that human values on individual level are the core for effective implementation of TQM. But despite the popularity of TQM, an absence of knowledge management framework that covers the tacit knowledge of human values identification and assessment for TQM implementation is limited. Human resource (HR) management work closely with quality management personals to motivate and socialize these values, but literature lacks in providing any directions for them about this tacit knowledge of human like values which are required for implementation of TQM. Without this, it is difficult for management to pursue the quality practices implementation. Thus, this research focused on this gap by proposing the knowledge management framework of human tacit knowledge like values identification and assessment for quality implementation. This research could assist HR and quality management to provide better understanding of human values and their level of practicing for implementation of TQM. Besides this, it may assist the HR management to perform the core HR functions such as selection, performance evaluation, and training and development that leads to the implementation of TQM.Â